Body mass index related to executive function and hippocampal subregion volume in subjective cognitive decline - Chen, Ruilin; Cai, Guiyan; Xu, Shurui; Sun, Qianqian; Luo, Jia; Wang, Yajun; Li, Ming; Lin, Hui; Liu, Jiao (Frontiers in Aging Neuroscience, 2022)
Objective This study aims to explore whether body mass index (BMI) level affects the executive function and hippocampal subregion volume of subjective cognitive decline (SCD). Materials and methods A total of 111 participants were included in the analysis, including SCD (38 of normal BMI, 27 of overweight and obesity) and normal cognitive control (NC) (29 of normal BMI, 17 of overweight and obesity). All subjects underwent the Chinese version of the Stroop Color-Word Test (SCWT) to measure the executive function and a high-resolution 3D T1 structural image acquisition. Two-way ANOVA was used to examine the differences in executive function and gray matter volume in hippocampal subregions under different BMI levels between the SCD and NC. Result The subdimensions of executive function in which different BMI levels interact with SCD and NC include inhibition control function [SCWT C-B reaction time(s): F(1,104) = 5.732, p = 0.018], and the hippocampal subregion volume of CA1 [F(1,99) = 8.607, p = 0.004], hippocampal tail [F(1,99) = 4.077, p = 0.046], and molecular layer [F(1,99) = 6.309, p = 0.014]. After correction by Bonferroni method, the population × BMI interaction only had a significant effect on the CA1 (p = 0.004). Further analysis found that the SCWT C-B reaction time of SCD was significantly longer than NC no matter whether it is at the normal BMI level [F(1,104) = 4.325, p = 0.040] or the high BMI level [F(1,104) = 21.530, p < 0.001], and the inhibitory control function of SCD was worse than that of NC. In the normal BMI group, gray matter volume in the hippocampal subregion (CA1) of SCD was significantly smaller than that of NC [F(1,99) = 4.938, p = 0.029]. For patients with SCD, the high BMI group had worse inhibitory control function [F(1,104) = 13.499, p < 0.001] and greater CA1 volume compared with the normal BMI group [F(1,99) = 7.619, p = 0.007]. Conclusion The BMI level is related to the inhibition control function and the gray matter volume of CA1 subregion in SCD. Overweight seems to increase the gray matter volume of CA1 in the elderly with SCD, but it is not enough to compensate for the damage to executive function caused by the disease. These data provide new insights into the relationship between BMI level and executive function of SCD from the perspective of imaging.